Reproducing Gender Inequality: A Critical Discourse Analysis of a Turkish Adult Literacy Textbook - Ramazan Gungor; Esther Prins (Adult Education Research Conference, 2010)
Based on Critical Discourse Analysis of a prominent adult literacy textbook in Turkey, this paper discusses the text’s two main Discourses: (a) a normative parenting Discourse that assigns mothers responsibility for childrearing and caretaking, and fathers responsibility for discipline; and (b) a Discourse of the sexual division of labor that associates the outside, public world with men, and the private, domestic world with women.